The Principal Leadership of the Implementation of Adiwiyata Program in Elementary School in Yogyakarta City - Purwati, Eni; Wibowo, Drs. Udik Budi (KnE Social Sciences, 2019)
Adiwiyata is one of national programs on environment preservation under the ministry of Enviroment on forest in order to encourage the creation of knowledge and consciousness of residents in enviromental preservation efforts. But the problems are limited human resources, lack of management and infrastructure, and less leadership. So, the purpose of this study is to describe the principal leadership towards the implementation of the adiwiyata program in the elementary schools. The method conducted was literature study, to build a foundation of theory, frame of thingking and theoritical hypothetis. The results of this study is to successfull implementation of adiwiya deepen on utilizing exiting human resources, to be more creative and skilled, socialization on the management of facilities and infrastructure in order to provide stock in term of facilities and infrastructure management, and is the problems occurred can be released the appropriate type of leadership that is using this type of transformational leadership. Keywords: leadership; adiwiyata; principal; facilities and infrastructure